Protection of Photosynthesis by UVR8 and Cryptochromes in Arabidopsis Under Blue and UV Radiation - Morales, Luis Orlando; Shapiguzov, Alexey; Rai, Neha; Aphalo, Pedro José; Brosché, Mikael (John Wiley & Sons, 2025)
Photosynthesis in plants is negatively affected by high light intensity and UV radiation. The photoreceptors UV RESISTANCE LOCUS 8 (UVR8) and CRYPTOCHROMES (CRYs) mediate perception and acclimation of plants to UV-B/UV-A2 (290–340 nm) and UV-A1/blue light (350–500 nm), respectively. However, their roles in photoprotection of photosynthesis across different wavebands of the spectrum remain unclear. Using chlorophyll fluorescence and LED lighting we studied the roles of UVR8 and CRYs in maintaining photosynthetic capacity in Arabidopsis exposed to UV-B, UV-A1, and blue light. Analysis of quantum yield of Photosystem II, nonphotochemical quenching, and LHCII phosphorylation demonstrated that CRYs preserve photosynthetic performance in plants exposed to UV-B, UV-A1, and blue light. UVR8 and CRYs exhibit partially redundant functions in maintaining photosynthetic activity under UV-B, UV-A1, and blue light, and in preventing photodamage under high UV-A1 irradiance. Impaired UVR8 and CRY signalling reduced epidermal flavonol accumulation in leaves, which further compromised photoprotection. These findings provide valuable insights into how UV and blue light perception contribute to photoprotection, with broad implications for plant performance both in natural and managed environments.
Keywords: Arabidopsis; blue light; cryptochromes; photoprotection; photosynthesis; UV radiation; UVR8